The atmospheric “skin” of the city - Tonino Griffero (Ambiances)
What is an urban atmosphere? Through an atmospherological (aesthetical-phenomenological) approach, primarily inspired by the new aesthetics (Böhme) and the new phenomenology (Schmitz), the paper investigates what creates the overall impression (imageability) of a city, if its atmosphere must necessarily be that of familiarity and how our dwelling-house can be understood as a real culture (or cultivation) of immersive atmospheres.